Comparative Effect of Different Polymerization Techniques on the Flexural and Surface Properties of Acrylic Denture Bases. Issue 4 (22nd May 2017) - Gad, Mohammed M.; Fouda, Shaimaa M.; ArRejaie, Aws S.; Al‐Thobity, Ahmad M.
Abstract: Purpose: Polymerization techniques have been modified to improve physical and mechanical properties of polymethylmethacrylate (PMMA) denture base, as have the laboratory procedures that facilitate denture construction techniques. The purpose of the present study was to investigate the effect of autoclave polymerization on flexural strength, elastic modulus, surface roughness, and the hardness of PMMA denture base resins. Materials and Methods: Major Base and Vertex Implacryl heat‐polymerized acrylic resins were used to fabricate 180 specimens. According to the polymerization technique, tested groups were divided into: group I (water‐bath polymerization), group II (short autoclave polymerization cycle, 60°C for 30 minutes, then 130°C for 10 minutes), and group III (long autoclave polymerization cycle, 60°C for 30 minutes, then 130°C for 20 minutes). Each group was divided into two subgroups based on the materials used. Flexural strength and elastic modulus were determined by a three‐point bending test. Surface roughness and hardness were evaluated with a profilometer and Vickers hardness (VH) test, respectively. One‐way ANOVA and the Tukey‐Kramer multiple‐comparison test were used for results analysis, which were statistically significant at p ≤ 0.05. Results: Autoclave polymerization showed a significant increase in flexural strength and hardness of the two resins ( p < 0.05). The elastic modulus showed a significant increase in the major base resin, while a significant decrease was seen for Vertex Implacryl in all groups ( p < 0.05); however, there was no significant difference in surface roughness between autoclave polymerization and water‐bath polymerization ( p > 0.05). Conclusion: Autoclave polymerization significantly increased the flexural properties and hardness of PMMA denture bases, while the surface roughness was within acceptable clinical limits. For a long autoclave polymerization cycle, it could be used as an alternative to water‐bath polymerization.